Improving Traders' and Buyers' Understanding of The Exchange Rate In Economic Transactions In The Border Market - Yolinda Yanti Sonbay; Beatrix Yunarti Manehat; Adiutrix Maria Irayanti Seran; Alfonsus Rodriques Suninono; Rere Paulina Bibiana; Eugenesius Hans Mbouk; Monica Pareira de Jesus; Afonso Alexio (International Journal Of Community Service, 2023)
This community service carried out at the Wini (Indonesia) border market and Regiao Administrativa Especial de Oecusse (Ambeno) Timor Leste. There are 3 problems that occur at the Wini border market, namely 1) During transactions, traders do not have a certain formula for determining and fixing exchange rates. Determining exchange rates in the market is only based on bargaining between sellers and buyers, 2) In the bargaining process, sellers and buyers do not see the exchange rate that applies when the transaction takes place and 3) traders in the border market determine the exchange rate during the transaction only following the exchange rate that has been made by other traders in the border market. The service was carried out using socialization methods and Focus Group discussions with 20 traders/buyers from Indonesia, Timor Leste and the governments of the two countries.The results of this community service provide understanding to buyers and sellers from two countries about the obligation to use the currency of the country where the transaction occurs, the importance of exchanging foreign money at a legal money changer, the rules regarding international trade, as well as an understanding of the basis for determining the selling value of products that bring business profits. . By doing business according to government regulations and international business standards, people in border markets can win profits.